Based on the Metabolomic Approach the Energy Metabolism Responses of Oriental River Prawn Macrobrachium nipponense Hepatopancreas to Acute Hypoxia and Reoxygenation - Sun, Shengming; Guo, Zhongbao; Fu, Hongtuo; Ge, Xianping; Zhu, Jian; Gu, Zhimin (Frontiers in Physiology, 2018)
Hypoxia represents a major physiological challenge for prawns and is a problem in aquaculture. Therefore, an understanding of the metabolic response mechanism of economically important prawn species to hypoxia and re-oxygenation is essential. However, little is known about the intrinsic mechanisms by which the oriental river prawn Macrobrachium nipponense copes with hypoxia at the metabolic level. In this study, we conducted gas chromatography-mass spectrometry-based metabolomics studies and assays of energy metabolism-related parameters to investigate the metabolic mechanisms in the hepatopancreas of M. nipponense in response to 2.0 O2/L hypoxia for 6 h and 24 h, and reoxygenation for 6 h following hypoxia for 24 h. Prawns under hypoxic stress displayed higher glycolysis-related enzyme activities and lower mRNA expression levels of aerobic respiratory enzymes than those in the normoxic control group, and those parameters returned to control levels in the reoxygenated group. Our results showed that hypoxia induced significant metabolomic alterations in the prawn hepatopancreas within 24 h. The main metabolic alterations were depletion of amino acids and 2-hydroxybutanoic acid and accumulation of lactate. Further, the findings indicated that hypoxia disturbed energy metabolism and induced antioxidant defense regulation in prawns. Surprisingly, recovery from hypoxia (i.e., reoxygenation) significantly affected 25 metabolites. Some amino acids (valine, leucine, isoleucine, lysine, glutamate, and methionine) were markedly decreased compared to the control group, suggesting that increased degradation of amino acids occurred to provide energy in prawns at reoxygenation conditions. This study describes the acute metabolomic alterations that occur in prawns in response to hypoxia and demonstrates the potential of the altered metabolites as biomarkers of hypoxia.